Myasthenia Gravis with Anti-Muscle-Specific Tyrosine Kinase Antibody during Pregnancy and Risk of Neonatal Myasthenia Gravis: A Case Report and Review of the Literature - Ken-ichi Inoue; Jun Tsugawa; Jiro Fukae; Kosuke Fukuhara; Hiroyasu Kawano; Shinsuke Fujioka; Yoshio Tsuboi (Case Reports in Neurology, 2020)
A 31-year-old woman presented with a nasal voice, dysarthria, and upper limb weakness during her first pregnancy. Soon after delivery of her first baby, her symptoms disappeared. At the age of 34 years, during her second pregnancy, her nasal voice re-appeared. After delivery of the second baby, her nasal voice worsened, and bilateral eyelid ptosis and easy fatigability were also evident. She was referred to our hospital. Because of her myasthenic symptoms and anti-muscle-specific tyrosine kinase (MuSK) antibody (Ab)-positive status, she was diagnosed as having myasthenia gravis (MG). Her symptoms were worse than those in her first pregnancy. She was treated with oral steroid and double filtration plasmapheresis. After initiation of treatment, her myasthenic symptoms improved completely. In addition, her baby developed transient neonatal MG (TNMG) on the fourth day after birth and then gradually recovered over 30 days. It should be noted that symptoms of patients with anti-MuSK Ab-positive MG (MuSK-MG) can deteriorate during pregnancy, and the babies delivered of patients with MuSK-MG have a high probability of developing TNMG.